Cavity-enhanced spectroscopy of a few-ion ensemble in Eu3+:Y2O3. (28th September 2018) - Casabone, Bernardo; Benedikter, Julia; Hümmer, Thomas; Oehl, Franziska; Lima, Karmel de Oliveira; Hänsch, Theodor W; Ferrier, Alban; Goldner, Philippe; Riedmatten, Hugues de; Hunger, David
Abstract: We report on the coupling of the emission from a single europium-doped nanocrystal to a fiber-based microcavity under cryogenic conditions. As a first step, we study the properties of nanocrystals that are relevant for cavity experiments and show that embedding them in a dielectric thin film can significantly reduce scattering loss and increase the light–matter coupling strength for dopant ions. The latter is supported by the observation of a fluorescence lifetime reduction, which is explained by an increased local field strength. We then couple an isolated nanocrystal to an optical microcavity, determine its size and ion number, and perform cavity-enhanced spectroscopy by resonantly coupling a cavity mode to a selected transition. We measure the inhomogeneous linewidth of the coherent 5 D 0 – 7 F 0 transition and find a value that agrees with the linewidth in bulk crystals, evidencing a high crystal quality. We detect the fluorescence from an ensemble of few ions in the regime of power broadening and observe an increased fluorescence rate consistent with Purcell enhancement. The results represent an important step towards the efficient readout of single rare earth ions with excellent optical and spin coherence properties, which is promising for applications in quantum communication and distributed quantum computation.